Baekdudgegan the great Baekdu meridian [videorecording] - Jung, Hyung Gun; Kim, Ki-Dong; On, Seung-In (Timeless journey)
A journey to the mountain range from Mount Chini, Mount Dukyu, Mount Taebaek, Mount Odoe and Mount Surak. A look at the traditional tea house and the buddhist ritual.